2011
DOI: 10.1182/blood-2011-04-351437
|View full text |Cite
|
Sign up to set email alerts
|

Bone microstructural changes revealed by high-resolution peripheral quantitative computed tomography imaging and elevated DKK1 and MIP-1α levels in patients with MGUS

Abstract: Recent population-based studies demonstrate an increased fracture risk with monoclonal gammopathy of undetermined significance (MGUS). The etiology of this increased risk remains unclear, however, because areal bone mineral density (aBMD) measurements by dualenergy x-ray absorptiometry cannot assess bone microstructural properties critical to determining bone quality and strength. To better define the skeletal effects of MGUS, we performed aBMD and high-resolution peripheral quantitative computed tomography vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 35 publications
(43 reference statements)
1
63
1
Order By: Relevance
“…Although the markers identified in our study have been identified previously in clinical studies of MM or its precursor states ( i.e ., MGUS and SMM),45, 46, 47, 48, 49, 50 the direction of our findings is in general opposite to observations among subjects diagnosed with MM, where higher concentrations of these markers seems to be related to generally poorer disease outcome. The reason for this difference in direction of the effect is not known but may hint toward a preclinical deregulation of these important biological systems in subjects developing MM later in life which at the time of clinical manifestation reverse in overexpression.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the markers identified in our study have been identified previously in clinical studies of MM or its precursor states ( i.e ., MGUS and SMM),45, 46, 47, 48, 49, 50 the direction of our findings is in general opposite to observations among subjects diagnosed with MM, where higher concentrations of these markers seems to be related to generally poorer disease outcome. The reason for this difference in direction of the effect is not known but may hint toward a preclinical deregulation of these important biological systems in subjects developing MM later in life which at the time of clinical manifestation reverse in overexpression.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are in accordance with the findings of Ng et al, wherein DXA measurements on 50 MGUS patients, compared with 100 controls, showed no significant difference in areal BMD at lumbar spine, femur neck, or total radius, although they did find a significant difference in areal BMD at total femur. 16 In a previous large screening study, a 20% increased risk for a diagnosis of osteoporosis was found in individuals with MGUS. 6 This is contradictory to our results, but might be explained by the increased surveillance of individuals with MGUS, thus leading to more investigations (DXA scans) and diagnoses of osteoporosis, and not necessarily indicating a lower BMD in the group.…”
Section: Discussionmentioning
confidence: 99%
“…26.3 mg/L). 1 A total of 39 individuals were excluded from analysis due to previous lymphoproliferative disease at baseline (21), missing blood sample (16), missing consent form (1), or M-protein concentration above the limit for MGUS (1).…”
Section: Mgus and Lc-mgus Diagnosismentioning
confidence: 99%
See 2 more Smart Citations